Hermeneutika Ruhullah Khomeini: Surplus Makna dan Pembacaan Alegoris Terhadap Term Al-Rahman dan Al-Rahim - Rosalnia, Rika Leli Dewi Khusaila; Isnaini, Subi Nur (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
The interpretation of Ruhullah Khomeini which is agreed upon as a Sufistic interpretation is interesting for further discussion. This paper attempts to explore Imam Khomeini’s hermenutics, starting from his paradigm of the Qur’an and its exegesis, then examines his theory of allegorical interpretation by looking at how it produces new meanings that go beyond the literal meaning of the text or reach esoteric meanings, especially in terms of al-raḥmān and al-raḥīm. This paper use Paul Ricoeur’s interpretation theory as a thinking partner to find the idea of a surplus meaning that inhernt in every single text, including the Qur’anic text. This research finds three main points: Imam Khomeini’s idea on the diversity of meanings as a logical consequence from the premise that the Qur’an has two meanings, exoteric and esoteric; allegorical interpretation of Imam Khomeini which is explained discursively depicting a Sufistic-philosophical face and colored by Shia ideology; the interpretation of the terms al-raḥmān and al-raḥīm presents the concept of wujūdīyah (the existence) as a result of synthesis from the concepts of previous philosophers, especially Ibn ‘Arabī and Mulla Sadra. The diversity of meanings of al-raḥmān and al-raḥīm shown in Imam Khomeini’s interpretation from several views and his personal synthesis, includes: the two terms are interpreted the same and the repetition is only confirmation, meaning compassion and kindness, the Names and Attributes of Allah that reach the level of existence and manifestation.